Comparative biological impacts of an aerosol from carbon-heated tobacco and smoke from cigarettes on human respiratory epithelial cultures: A systems toxicology assessment. (May 2018) - Iskandar, Anita R.; Martin, Florian; Leroy, Patrice; Schlage, Walter K.; Mathis, Carole; Titz, Bjorn; Kondylis, Athanasios; Schneider, Thomas; Vuillaume, Grégory; Sewer, Alain; Guedj, Emmanuel; Trivedi, Keyur; et al.
Abstract: The biological impact of an aerosol of a potential modified-risk tobacco product, carbon heated tobacco product 1.2 (CHTP1.2), was comprehensively assessed for the first time in vitro using human small airway and nasal epithelial models following a systems toxicology approach. The potentially reduced effects of CHTP1.2 aerosol exposure were benchmarked against those of 3R4F cigarette smoke at similar nicotine concentrations. Experimental repetitions were conducted for which new batches of small airway and nasal cultures were exposed to CHTP1.2 aerosol or 3R4F smoke for 28 minutes. The biological impacts were determined based on a collection of endpoints including morphology, cytotoxicity, proinflammatory mediator profiles, cytochrome P450 1A1/1B1 activity, global mRNA and microRNA changes and proteome profiles. Alterations in mRNA expression were detected in cultures exposed to CHTP1.2 aerosol, without noticeable morphological changes and cytotoxicity, and minimal impact on proinflammatory mediator and proteome profiles. The changes linked to CHTP1.2 aerosol exposure, when observed, were transient. However, the impact of 3R4F smoke exposure persisted long post-exposure and greater than CHTP1.2 aerosol. Morphological changes were observed only in cultures exposed to 3R4F smoke. The lower biological effects of CHTP1.2 aerosol than 3R4F smoke exposure were observed similarly in both small airway and nasal epithelial cultures. Graphical abstract: Highlights: Aerosols of a heat-not-burn tobacco product elicited lower impacts compared with smoke of 3R4F reference cigarettes. Systems toxicology revealed changes at the cellular–molecular levels not otherwise apparent from morphological features. The reduced impact of heated tobacco aerosols on small airway was similar than that on nasal epithelial cultures.